Analisis Risiko Keselamatan Kerja Menggunakan Metode HIRADC pada Proses Produksi di PT. XYZ - Ahmad Hidayat Nurwahid Hasyim; Helmi Asril Rayhandi Putra; Dinda Olivia Nur’Aini; Salsabil Nabila Azzahra; Regita Putri Cahyati; Muhammad Azhar Hafiz Ghiffari; Anis Rohmana Malik (Pusat Riset dan Inovasi Nasional, 2025)
Occupational safety and health (OSH) is a crucial aspect in the manufacturing industry due to the high potential hazards that can occur during the production process. This study aims to identify potential hazards, assess risk levels, and design control measures using the HIRADC method (Hazard Identification, Risk Assessment, and Control Determination) in the production process at PT XYZ. This research employs a qualitative approach with data collection techniques including direct observation and interviews with management and workers. The analysis results indicate five main hazard priorities, namely physical hazards (noise, heat, and harmful particles), chemical hazards (exposure to toxic substances from welding and painting processes), mechanical hazards (heavy machinery and cutting tools), ergonomic hazards (non-ergonomic work postures and manual lifting), and electrical hazards (non-standard installations and risk of electric shock). Each of these hazards is controlled through the implementation of SOPs, the use of personal protective equipment (PPE), safety training, as well as improvements in facilities and work layout. The application of the HIRADC method has proven effective in mapping risks and formulating control strategies to create a safe and productive work environment.